Intimate Terrorism and Situational Couple Violence in General Surveys: Ex-Spouses Required. (February 2014) - Johnson, Michael P.; Leone, Janel M.; Xu, Yili
In this article, we argue that past efforts to distinguish among types of intimate partner violence in general survey data have committed a critical error—using data on current spouses to develop operationalizations of intimate terrorism and situational couple violence. We use ex-spouse data from the National Violence Against Women Survey (NVAWS) to develop new operationalizations. We then demonstrate that NVAWS current spouse data contain little intimate terrorism; we argue that this is likely to be the case for all general surveys. In addition, the ex-spouse data confirm past findings regarding a variety of differences between intimate terrorism and situational couple violence, including those predicted by feminist theories.